Android game programming for dummies - James, Derek (For Dummies., 2013)
Get your head in the game and start developing engaging Android apps that game gurus will love! A bit of Java knowledge is helpful, but even if you lack that, this book will walk you through creating two Android games and getting them into Google Play. Once you've got the basics down, let your imagination lead the way!